Thermal Runaway: Identifying the Cause of Rupture of Li‐Ion Batteries during Thermal Runaway (Adv. Sci. 1/2018). Issue 1 (17th January 2018) - Finegan, Donal P.; Darcy, Eric; Keyser, Matthew; Tjaden, Bernhard; Heenan, Thomas M. M.; Jervis, Rhodri; Bailey, Josh J.; Vo, Nghia T.; Magdysyuk, Oxana V.; Drakopoulos, Michael; Di Michiel, Marco; Rack, Alexander; et al.
Abstract : At a critical temperature, active materials within Li‐ion batteries break down, generating heat and gas. Thermal runaway occurs when this process accelerates after the temperature of the cell begins to rise, leading to hazardous failure mechanisms such as the cell bursting. In article number1700369, Paul R. Shearing and co‐workers use high‐speed X‐ray imaging to capture and characterize such high risk mechanisms in commercial cell designs.